Avaliação da atividade biológica do material orgânico derivado da base de Schiff N,N-bis'(salicilideno)-1,2-fenilenodiamina complexado com cobre (ll) e cobalto (ll) - Soriano, Bianca (Universidade Federal de São Carlos, 2021)
Treatment for bacterial infections is through antimicrobials and resistance is a major worldwide problem that leads to approximately 35,000 deaths per year. Another public health problem is related to occurrences caused by parasites such as visceral leishmaniasis, which presents severe clinical manifestations that can lead to death and the available treatments can cause definite side effects in addition to resistance. In this way, there is a need to produce new substances for the pharmacological development of molecules and their derivatives. This study aimed to evaluate the physical and biological properties of products derived from the base of Schiff N, N’-bis (Salicylidene) -1,2-phenylenediamine complexed with copper (II) and cobalt (II). X-ray diffraction techniques, Ramam spectroscopy, Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (CBM), time kill, modulation of antibiotics with amikacin and gentamicin, determination of leishmanicida, determination of cell cytotoxicity in fibroblasts and evaluation of production of Reactive Oxygen Species (ROS). It was possible to identify differences between the free ligand and its criteria. In the antimicrobial activity, the most expressive results were obtained with the Gram-positives S. aureus, S. epidermidis, S. saprophyticus, M. luteus, E. faecalis and B. subitilis with inhibitions between 75 and 96% for all tested and a MIC of 125 µg.ml-1 to these bacteria. The CBM obtained was 1000 µg.ml-1 and 250 µg.ml-1 to S. aureus and S. epidermidis, respectively. To S. saprophyticus and E. faecalis, 500 µg.ml- 1 was detected. Through the antibiotic modulation test, a synergistic effect of the free ligand with the antibiotics gentamicin and amikacin was detected, reducing the MIC by 4 and 16X. In the evaluation of the leishmanicidal activity, activity was observed in the highest tested concentration of the studies with inhibitions above 85%. The assessment of cytotoxicity allowed us to observe that the free ligand has lower toxicity for all cell types tested when compared to the complexes. Through the ROS test, ROS production was detected, but at the lowest concentration tested, this production reached levels close to the levels of the control group. Through the cell migration test, total cell growth was detected in 48 hours with the free ligand and 72 hours with the cobalt complex. Thus, the data suggest that the cobalt complex and the free ligand have expressive antimicrobial and leishmanicidal activity when compared to the copper complex.
Evaluation of the biological activity of organic material derived from the Schiff base N,N-bis'(salicylidene)-1,2-phenylenediamine complexed with copper (ll) and cobalt (ll)
Keywords: Atividade antimicrobiana; Atividade Leishmanicida; Base de Schiff; Complexos metálicos; Antimicrobial activity; Leishmanicidal activity; Schiff's base; Metal complexes; CIENCIAS BIOLOGICAS::MICROBIOLOGIA